2013
DOI: 10.1108/ejm-12-2010-0665
|View full text |Cite
|
Sign up to set email alerts
|

Influence of consumer online resale awareness on purchase decisions: a mental accounting perspective

Abstract: Purpose -Consumer online resale is becoming an increasingly common method of both buying and selling goods. When an item can be easily resold online, consumers' subjective estimation of the value of that item changes in complex ways based on consumption cost and resale return. This in turn can affect consumers' decisions to purchase new products. The authors aim to apply the principles of mental accounting to investigate how consumers' economic psychology associated with buying a new product is affected when a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 31 publications
2
33
0
1
Order By: Relevance
“…Nevertheless, other authors consider both terms, social commerce and social shopping as analogous (Sun, 2011;Liao & Chu, 2013). In our case, we will not consider social commerce and social shopping as equal as we have found evidences on researches in which social shopping is defined as "the enjoyment of shopping with friends and family, socializing while shopping, and bonding with others while shopping" (Hassouneh & Brengman, 2011;Lee et al, 2013;Ozen & Engizek, 2014) in which socialization and enjoyment are the key of the concept, and there is no evidence of interactive social relationships within the concept which lead us to think that social shopping is related with Web 2.0 or e-commerce whatsoever.…”
Section: Contextualization Of Social Commerce As a New Trend In Commementioning
confidence: 99%
“…Nevertheless, other authors consider both terms, social commerce and social shopping as analogous (Sun, 2011;Liao & Chu, 2013). In our case, we will not consider social commerce and social shopping as equal as we have found evidences on researches in which social shopping is defined as "the enjoyment of shopping with friends and family, socializing while shopping, and bonding with others while shopping" (Hassouneh & Brengman, 2011;Lee et al, 2013;Ozen & Engizek, 2014) in which socialization and enjoyment are the key of the concept, and there is no evidence of interactive social relationships within the concept which lead us to think that social shopping is related with Web 2.0 or e-commerce whatsoever.…”
Section: Contextualization Of Social Commerce As a New Trend In Commementioning
confidence: 99%
“…This is problematic because consumers are known to operate in a different manner and they are motivated by different drivers when making purchasing decisions related to new versus second-hand products (Cervellon et al, 2012;Guiot & Roux, 2010;Xu, Chen, Burman, & Zhao, 2014). The more attractive and efficient the second-hand market becomes, the more it affects those who buy brand-new products (Chu & Liao, 2010;Liao & Chu, 2013). This knowledge is also relevant for the products sold in the primary markets.…”
mentioning
confidence: 99%
“…This knowledge is also relevant for the products sold in the primary markets. The more attractive and efficient the second-hand market becomes, the more it affects those who buy brand-new products (Chu & Liao, 2010;Liao & Chu, 2013).…”
mentioning
confidence: 99%
“…Many previous studies indicated that mental accounting had effect on customer decision making (Duxbury et al, 2005;Helion & Gilovich, 2014;Ho Ha et al, 2006). Liao and Chu (2013)investigated the mental accounting related to buying a new product given different levels of awareness of the possibility of reselling and buying similar, different, or identical products. Promotion is divided into two categories according to incentives (Campbell & Diamond, 1990).…”
Section: 3the Moderating Role Of Mental Accountingmentioning
confidence: 99%